CHILDHOOD SEXUAL ABUSE IMPACT ON ADULTHOOD - Triyanto, Annisa Ayu Permata (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2024)
Introduction – Child sexual abuse (CSA) occurs when a kid or younger person is forced or persuaded to engage in sexual activity, whether the child is conscious of what is taking place. According to global databases, in one-third of countries in the world, at least 5% of young women reported experiences of sexual abuse in childhood. Mental health issues, behavioral manifestations, and interpersonal outcomes are a few impacts of CSA. This study aims to discuss the CSA's impact on adulthood. Methods – The researcher used a total of 13 works of literature, articles, and journals that discuss CSA and its correlation with some mental health issues impact on an adult. Results – Adults with a history of CSA are more likely to suffer from early onset depression, borderline personality disorder, and suicidal tendencies than someone without a history, that is why emotional support seems very important to the CSA survivors. Discuss – As children are sexually abused, it may lead to a variety of difficulties with relationships in general, as well as a host of poor intimate relationship consequences such as adult sexual assault, intimate partner violence, and reduced happiness in romantic relationships. Conclusion – Childhood sexual abuse is still a major problem among children and has several psychological impacts on adulthood, and emotional support is one of the great therapies. Keywords: childhood, sexual, abuse.